2016
DOI: 10.1021/acsnano.6b06582
|View full text |Cite
|
Sign up to set email alerts
|

Separation, Sizing, and Quantitation of Engineered Nanoparticles in an Organism Model Using Inductively Coupled Plasma Mass Spectrometry and Image Analysis

Abstract: The increased use of engineered nanoparticles (ENPs) in consumer products and the relative lack of understanding of their associated hazards necessitate further investigation of the interactions between ENPs and environmental and biological systems. For environmental studies assessing uptake of orally ingested ENPs, a key step in ensuring accurate quantification of ingested ENPs is efficient separation of the organism from ENPs that are either nonspecifically adsorbed to the organism and/or suspended in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 57 publications
(125 reference statements)
0
34
0
Order By: Relevance
“…[6-8, 10, 11, 15, 16] When our research group tested and employed a similar rinsing strategy, we found that water rinsing was unsuitable for the efficient removal of non-ingested NPs, even at low, environmentally relevant exposure concentrations (ng mL -1 or part per billion in gold mass fraction). [17] Therefore, it was necessary to devise a postexposure rinsing strategy that, unlike conventional water rinsing protocols, ensured greater efficiency in regard to the removal of excess, non-ingested ENPs.…”
Section: Principles and Scopementioning
confidence: 99%
See 4 more Smart Citations
“…[6-8, 10, 11, 15, 16] When our research group tested and employed a similar rinsing strategy, we found that water rinsing was unsuitable for the efficient removal of non-ingested NPs, even at low, environmentally relevant exposure concentrations (ng mL -1 or part per billion in gold mass fraction). [17] Therefore, it was necessary to devise a postexposure rinsing strategy that, unlike conventional water rinsing protocols, ensured greater efficiency in regard to the removal of excess, non-ingested ENPs.…”
Section: Principles and Scopementioning
confidence: 99%
“…[3,24,25] However, sucrose density gradient centrifugation (SDGC) separation had not been employed until recently for the separation of C. elegans from NPs after exposure. [17] This protocol details an SDGC procedure for the efficient separation of AuNPs from C. elegans.…”
Section: Principles and Scopementioning
confidence: 99%
See 3 more Smart Citations